PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN DIVERSIFIKASI PRODUK OLAHAN IKAN GABUS DAN PISANG DI DESA PASIR PUTIH KABUPATEN KUBU RAYA - Gunarto Gun; Doddy Irawan; Eko Julianto; Muhammad Iwan (LPPM STAI Muhammadiyah Probolinggo, 2026)
Pasir Putih Village, located in Teluk Pakedai District, Kubu Raya Regency, possesses considerable local resources in the form of snakehead fish and bananas that have not been optimally utilized by the community. The limited skills and knowledge of the local community in processing these commodities have resulted in low economic added value. This community engagement program aimed to enhance community knowledge and practical skills through training on the diversification of processed snakehead fish and banana products. The program was implemented through several stages, including needs assessment, program planning, hands-on training, mentoring, and activity evaluation. The target participants were members of the local Family Welfare Empowerment (PKK) group. The results demonstrated a significant improvement in participants’ understanding and practical abilities in processing snakehead fish into fish cakes (pempek) and bananas into banana chips. In addition, the program increased community motivation to develop household-based enterprises utilizing local resources. The product diversification training is expected to contribute to strengthening family income and supporting the sustainable development of community-based micro-enterprises.